TECHNOLOGICAL TOOLS IN EFL CLASS - Ramli Ramli; Andi Hamzah Fansury; Vivit Rosmayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Mobile-assisted Language Learning (MALL) and IoT technology have revolutionized language learning approaches, bringing a new level of flexibility and accessibility to the field. Technological Pedagogical Content Knowledge (TPACK) is a framework for enhancing teacher knowledge and teaching practices in educational contexts. It emphasizes the integration of teacher competencies and the development of Information and Communication Technology (ICT) in language teaching and learning. Some technologies have been integrated into teaching and learning English and effectively enhance language learning experiences, improve language skills, and provide flexibility and accessibility in language education, reflecting a growing interest in leveraging mobile technologies to support EFL instruction, such as LMS, YouTube, podcasts and vodcasts, Kahoot, AI-powered technologies, digital whiteboards, and conferences. Teachers' attitudes, beliefs, and self-efficacy can inform professional development initiatives and instructional strategies for enhancing technology integration in educational settings